Anodic Oxidation of Industrial Winery Wastewater Using Different Anodes - Salazar-Gonzalez, R; Garcia-Mena, V; Huilinir-Curio, C; Lauzurique-Guerra, y (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Winery wastewater represents the largest waste stream in the wine industry. This deals with the mineralization of the organic matter present in winery wastewater using anodic oxidation and two types of anodes—namely, a boron-doped diamond electrode (BDD) and two mixed metal oxides (MMO), one with the nominal composition Ti/Ru0.3 Ti0.7 O2 and the other with Ti/Ir0.45 Ta0.55 O2. To conduct the study, the variability of different quality parameters for winery wastewater from the Chilean industry was measured during eight months. A composite sample was treated using anodic oxidation without the addition of supporting electrolyte, and the experiments were conducted at the natural pH of the industrial wastewater. The results show that this effluent has a high content of organic matter (up to 3025 ± 19 mg/L of total organic carbon (TOC)), which depends on the time of the year and the level of wine production. With MMO electrodes, TOC decreased by 2.52% on average after 540 min, which may be attributed to the presence of intermediate species that could not be mineralized. However, when using a BDD electrode, 85% mineralization was achieved due to the higher generation of hydroxyl radicals. The electrolyzed sample contained oxamic, acetic, and propionic acid as well as different ions such as sulfate, chloride, nitrate, and phosphate. These ions can contribute to the formation of different species such as active species of chlorine, persulfate, and perphosphate, which can improve the oxidative power of the system. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.